Use of newly isolated phages for control of Pseudomonas aeruginosa PAO1 and ATCC 10145 biofilms - Pires, D (2013)
Pseudomonas aeruginosa is a relevant opportunistic pathogen involved in nosocomial infections that frequently shows low antibiotic susceptibility. One of its virulence factors is associated with the ability to adhere to surfaces and form virulent biofilms. This work describes the isolation and characterization of lytic phages capable of infecting antibiotic-resistant P. aeruginosa strains. In addition, characterization of P. aeruginosa biofilms and the potential of newly isolated phages for planktonic and biofilm control was accessed. According to the results, the isolated phages showed different spectra of activity and efficiency of lysis. Four broad lytic phages were selected for infection of planktonic cells; however, despite their broad range of activity, two of the selected phages failed to efficiently control planktonic cultures. Therefore, only two phages (phiIBB-PAA2 and phiIBB-PAP21), highly capable of causing strong biomass reduction of planktonic cells, were tested against 24 h biofilms using a m.o.i. of 1. Both phages reduced approximately 1-2 log the biofilm population after 2 h of infection and reduction was further enhanced after 6 h of biofilm infection. However, biofilm cells of P. aeruginosa PAO1 acquired resistance to phiIBB-PAP21; consequently, an increase in the number of cells after 24 h of treatment was observed. Conversely, phage phiIB-PAA2 for P. aeruginosa ATCC10145 continued to destroy biofilm cells, even after 24 h of infection. In these biofilms, phages caused a 3 log reduction in the number of viable counts of biofilm cells.